Spread of genetically similar noroviruses in Bangkok, Thailand, through symptomatic and asymptomatic individuals. Issue 10 (October 2021) - Boonyos, Patcharaporn; Boonchan, Michittra; Phattanawiboon, Benjarat; Nonthabenjawan, Nutthawan; Tacharoenmuang, Ratana; Gunpapong, Ratigorn; Singchai, Phakapun; Upchai, Sompong; Rungnobhakhun, Pimpha; Mekmullica, Jutarat; Towayunanta, Worakarn; Chuntrakool, Kobkool; et al.
Abstract: Norovirus infection is a major cause of acute gastroenteritis, although some infected individuals are asymptomatic. GII.4 is the predominant genotype worldwide and, since 2000, has been the most prevalent in patients in Thailand with acute gastroenteritis. We screened stool samples for norovirus in 786 patients with acute gastroenteritis who were admitted to a hospital in Bangkok from 2017 to early 2019 and detected it in 136 specimens (17.3%). Eight and 124 specimens were positive for the GI and GII genogroups, respectively, and the remaining 4 specimens were double-positive. Nine genotypes (GI.3, GI.5, GII.2, GII.3, GII.4, GII.6, GII.8, GII.13, and GII.17) were identified from 140 strains, and 72 strains (51.4%) were GII.4. We had previously conducted a one-year survey of norovirus infection in residents of a community in Bangkok from May 2018 to April 2019 and found that a substantial portion of the residents were infected asymptomatically. The 9 genotypes identified in the patients were also commonly identified in the community residents. To investigate the relationship between noroviruses identified in the acute gastroenteritis patients and those identified in the community residents, phylogenetic tree analysis was conducted. Of the 9 genotypes, 8 showed similarities in both their genomic sequences and their deduced amino acid sequences. In addition, strain replacement of GI.3 was observed in both the patients and the community residents within the overlapping period. These results suggested that norovirus spreads efficiently to the community by simultaneously causing symptomatic and asymptomatic infections. Highlights: GII.4 Sydney predominated in gastroenteritis patients of Bangkok during 2017–2019. Common norovirus genotypes spread in symptomatic and asymptomatic individuals. Noroviruses in symptomatic and asymptomatic individuals share genetical similarity. Abstract : Norovirus; Symptomatic infection; Asymptomatic infection.